Strategi Marketing Produk Mi Lemonilo Di Instagram Menggunakan GRUP K-POP NCT Dream Sebagai Brand Ambassador - Khuyaimah; Hamidah; Muslimin (CV. ITTC INDONESIA, 2023)
One of the marketing strategies used by companies today is digital marketing through Instagram social media, there are factors to influence reciprocal behavior towards marketing products, one of which is the presence of Korean culture that enters Indonesia. From this phenomenon, several companies in the industrial business field are competing to attract public attention by bringing Korean artists to carry out potential collaborations through product marketing. Lemonilo officially announced the form of his product collaboration with a boy band from South Korea, namely NCT ​​Dream as Lemonilo's brand ambassador. This study aims to find out (1) How is the